2022
DOI: 10.1186/s44147-022-00132-1
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to creating semi-artificial city driving cycle: case study of Istanbul

Abstract: This study describes the methodology of creating Semi - Artificial City Cycle (SACC), which can be used for emission tests of road vehicles; sustainability of hybrid electric vehicle (HEV); or emission inventories of the city. This methodology uses the half-hour frequency traffic data of Istanbul to calculate the average speeds and travel distances of urban, rural and highway segments. Then, calculated average data convert into instantaneous time—velocity distribution by random time—speed values, which are app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…varies from city to city or regionally [15]. Aydin and Soruşbay [16] created the driving cycles of İstanbul city called Artificial Istanbul Driving Cycle based on average real traffic data. They showed that the İstanbul cycles resulted in lower CO 2 emission factors than those of the WLTC for segments of rural, urban, and highway.…”
Section: Introductionmentioning
confidence: 99%
“…varies from city to city or regionally [15]. Aydin and Soruşbay [16] created the driving cycles of İstanbul city called Artificial Istanbul Driving Cycle based on average real traffic data. They showed that the İstanbul cycles resulted in lower CO 2 emission factors than those of the WLTC for segments of rural, urban, and highway.…”
Section: Introductionmentioning
confidence: 99%